Oral myiasis of maxilla and mandible: A case report - Shruti A Shah; Sonali G Kadam; Dimple S Padawe; Vilas S Takate (Wolters Kluwer Medknow Publications, 2015)
Oral myiasis is a rare parasitic infestation of the house fly in the oral cavity. It is found in cases of extreme neglect of oral hygiene. Here is a case report of a 24-year-old female patient with history of cerebral palsy since childhood, affected with oral myiasis simultaneously affecting the maxilla as well as mandible. This case reports gives an overview of the clinical features of this distressing disease and also throws light on its treatment with a combination of conventional therapy and new drug Ivermectin.